2014
DOI: 10.4269/ajtmh.13-0582
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Samples and Methods in Chronic Cutaneous Leishmaniasis

Abstract: Abstract. This study aimed at finding out the most effective clinical samples and methods in chronic cutaneous leishmaniasis (CCL). Smear, aspiration fluid, and filter paper samples were taken from 104 skin lesions of suspected cases with CCL, and they were compared using microscopic examination, culture, and molecular methods. We characterized four different forms of CCL and identified the causative agents in CCL forms using high-resolution melting curve real-time polymerase chain reaction assay. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…Articles were excluded at this stage due to (i) articles not available, (ii) not in the field of interest, (iii) use of an inappropriate reference standard, and (iv) inability to complete a 2-by-2 contingency table. A total of 13 articles were included in the systematic review [5,[12][13][14][15][16][17][18][19][20][21][22][23] while data of 12 articles were included in the meta-analysis. Data of 1 article were not considered in the meta-analysis because they did not fit the respective subgroups for molecular method and/or sample type.…”
Section: Included Studiesmentioning
confidence: 99%
“…Articles were excluded at this stage due to (i) articles not available, (ii) not in the field of interest, (iii) use of an inappropriate reference standard, and (iv) inability to complete a 2-by-2 contingency table. A total of 13 articles were included in the systematic review [5,[12][13][14][15][16][17][18][19][20][21][22][23] while data of 12 articles were included in the meta-analysis. Data of 1 article were not considered in the meta-analysis because they did not fit the respective subgroups for molecular method and/or sample type.…”
Section: Included Studiesmentioning
confidence: 99%
“…It achieves sensitivities and specificities of up to 100% [26,27]. The novel qPCR achieved a lower LOD than cPCR, an outcome seen in other Leishmania assays utilising various targets [14,28,29]. Our future studies will determine the clinical sensitivity of samples previously tested positive for visceral leishmaniasis, to complement the clinical data obtained here.…”
Section: Discussionmentioning
confidence: 65%
“…Several molecular tests have been used to improve the diagnosis of CL 40,41 ; however, PCR has been found to offer high sensitivity and specificity compared with traditional parasitological methods 37 and can detect parasite DNA in a variety of clinical samples, 6,38 including direct smears, [42][43][44] Flinders Technology Associates filter paper, 45 and swabs from the lesion. 46 In many cases, the efficacy of PCR depends on the DNA extraction process, the number of copies of the molecular marker selected, and the type of PCR used (PCRrestriction fragment length polymorphism, conventional PCR, or qPCR).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a report by Tiwananthagorn et al 58 concluded that a PCR-kDNA assay was more sensitive than PCR-ITS and LAMP with the 18S rRNA gene. 42 Therefore, a comprehensive study to evaluate these parameters in a vast set of Leishmania species causing CL in the New World is needed.…”
Section: Discussionmentioning
confidence: 99%